2017
DOI: 10.1128/jvi.00499-17
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Lipoviroparticles Assemble in the Endoplasmic Reticulum (ER) and Bud off from the ER to the Golgi Compartment in COPII Vesicles

Abstract: Hepatitis C virus (HCV) exists as a lipoprotein-virus hybrid lipoviroparticle (LVP).In vitro studies have demonstrated the importance of apolipoproteins in HCV secretion and infectivity, leading to the notion that HCV coopts the secretion of very-low-density lipoprotein (VLDL) for its egress. However, the mechanisms involved in virus particle assembly and egress are still elusive. The biogenesis of VLDL particles occurs in the endoplasmic reticulum (ER), followed by subsequent lipidation in the ER and Golgi co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…This indicated that HULC plays an important role in regulating the efficient release of HCV particles. We additionally analysed the viral RNA using quantitative reverse transcription polymerase chain reaction (RT‐qPCR) method as explained earlier (Syed, Khan, Yang, & Siddiqui, ), to reaffirm that the effect observed in the infectivity assay amounts for the effect on HCV release. In support to our hypothesis, we found significant effect on the intracellular and extracellular viral RNA titre, which was in concert with the infectivity assay (Figure S2).…”
Section: Resultsmentioning
confidence: 92%
“…This indicated that HULC plays an important role in regulating the efficient release of HCV particles. We additionally analysed the viral RNA using quantitative reverse transcription polymerase chain reaction (RT‐qPCR) method as explained earlier (Syed, Khan, Yang, & Siddiqui, ), to reaffirm that the effect observed in the infectivity assay amounts for the effect on HCV release. In support to our hypothesis, we found significant effect on the intracellular and extracellular viral RNA titre, which was in concert with the infectivity assay (Figure S2).…”
Section: Resultsmentioning
confidence: 92%
“…This study is the first to document an essential role of the COPII machinery in HBV's pathogenic life cycle. HBV is yet another example of COPII cargo adaptor takeover by viral pathogens, encompassing VSV (Nishimura & Balch, ), the turnip mosaic virus (Jiang, Patarroyo, Garcia Cabanillas, Zheng, & Laliberte, ), HCV (Syed et al, ), and the Ebola virus (Yamayoshi et al, ). Together, those reports and our study add clues for pathogen‐specific exploitation of special COPII coats for host cell exit with potential implications for cell biology, virology, and antiviral drug designs.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens like the hepatitis C virus (HCV) and Ebola virus have been shown to utilize COPII as a transport mechanism for viral proteins en route to viral assembly and budding sites (Syed, Khan, Yang, & Siddiqui, ; Yamayoshi et al, ). Hence, the COPII machinery can become a distinct ally regarding pathogenic morphogenesis and release.…”
Section: Introductionmentioning
confidence: 99%
“…24 h post-nucleofection, medium was removed and cells were scraped into 2.5 ml ice cold PBS (without Ca2+ and Mg2+) supplemented with 10 µg/ml each of leupeptin, pepstatin, and chymostatin. Cells were spun down at 2,000 rpm for 3 min at 4°C and the pellets were resuspended in 1.5 ml ice cold Homogenization Buffer (250 mM Sucrose, 25 mM KCl, 10 mM HEPES pH=7.2, 1 mM EGTA, and 1x Sigma Fast Protease Inhibitor cocktail), as previously described (Syed et al, 2017). Cell suspensions were homogenized by passing through a 25-gauge syringe needle (10 times) and homogenates were centrifuged (600 g for 5 min) twice at 4°C.…”
Section: Methodsmentioning
confidence: 99%